(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2020)
The Valentín Formation (late Pleistocene-middle Holocene) outcrops in the Ullum-Zonda valley located in the south-central region of the Province of San Juan, in the Argentine Republic, about 20 km west of the capital city of San Juan. It is a tectonic depression in which two fold and thrust belts with different levels of detachment and opposite vergence converge and collide: to the west, the east verging thin-skinned Central Precordillera, and to the east, the west verging thick-skinned Eastern Precordillera (Rolleri, 1969; Baldis et al., 1979; Ortiz and Zambrano, 1981; Ramos, 1988, Allmendinger et al., 1990; Jordan et al., 1993; among others). The outcrops of the Valentín Formation have a surface area of 3.6 km2 and are scattered in an area of 110 km2 (Fig. 4) to the north, east, south, and southwest of the Ullum-Zonda valley. The paleoenvironmental evolution of these sequences is not yet clearly understood. Consequently, it has been almost impossible to determine the paleogeography and paleoclimatic conditions in this valley during the late Pleistocene-Holocene climatic transition. This study constitutes the first attempt to address this issue. Traditionally, the Valentín Formation has been interpreted as a lacustrine-palustrine environment associated with the San Juan River (e.g., Groeber and Tapia, 1926; Pandolfo, 1975; Salinas, 1979; García, 1996; Colombo et al., 2000; Suvires and Gamboa, 2011; Blanc, 2014; Blanc and Perucca, 2017; among others), an antecedent stream that descends from the Andes Cordillera. Following the three-component scheme to represent sediment movement along mountain valleys in Precordillera from Suriano et al. (2014) (Fig. 3), the San Juan River behaves as a sedimentary transference system for the intermountain basins developed along the narrow axial valleys between the numerous ranges of the Precordillera. This river has a glacial-nival regime with the peak of maximum runoff between December and January. It has an average annual flow of 60 m3/sec (Subsecretaría de Recursos Hídricos, 2004), registering millenary floods that can exceed 1,000 m3/sec (Perucca and Esper, 2009). In this study, we introduce a lithofacial, stratigraphic and paleoenvironmental analysis of the Valentín Formation together with a paleogeographic and paleoclimatic characterization of the Late Pleistocene and Early to Mid-Holocene in the Ullum-Zonda tectonic depression, based on sedimentological, geomorphological, and geochronological data (conventional radiocarbon, AMS, and OSL). Following the scheme proposed by Blanc and Perucca (2017; Fig. 4), the study area was divided into six sectors based on the spatial distribution of the Valentín Formation outcrops to facilitate a neat description and analysis. We carried out a detailed lithofacies analysis (Tables 2, 3, and 4) in five stratigraphic logs in sectors 1 (logs PB-VI and PB-COU), 2 (PB-FVZ log), and 5 (logs PB-DS1 and PB-DS2) (Fig. 5), and control observations in sectors 3, 4, and 6. Log description and analysis were made using the methodology proposed by Miall (1977), Allen (1983), Miall (1985; 1996; 2006) with modifications. The data obtained for the characterization of facies included: the thickness of horizons or layers, limiting surfaces, texture, structure, and carbonates. The texture was determined using classical soil manipulation methods to analyze its plasticity (Thien, 1979). The relative content of CaCO3 was determined from the sediment reaction (weak, moderate, or strong) in HCl diluted to 10%. Genetically related facies were grouped into facies associations (Table 3) considering as such a body of rock larger than a facies, characterized by its geometry (internal and external), the arrangement of its limiting surfaces (in the case of architectural elements), and the facies that compose it (Miall, 1977; Allen and Allen, 2005; Bridge and Demicco, 2008). Sixteen facies associations were defined and grouped into eight subenvironments representative of five sedimentary environments (Table 4). The geomorphological analysis consisted of the study of the landforms using satellite images, aerial photos, and digital elevation models (DEM of the Argentinian National Geographic Institute of 5 and 30 m resolution) together with field surveys where we observed the contact relationships between the different landforms and their morphogenetic processes. For the geochronological analysis, we used available numerical ages (Blanc and Perucca, 2017) (Table 1) from 14C dating of organic sediments by conventional and AMS techniques. Based on the obtained data, we constructed an artistic “paleo-satellite image” of the Ullum-Zonda valley using photographic montage techniques to approximately represent the paleogeography of this valley for the early Holocene (Greenlandian, 9,300 years BP) (Fig. 10). Blanc and Perucca (2017) divided the Valentín Formation into two chronostratigraphic units: a late Pleistocene age (16,700–15,200 years BP) unit and an early to middle Holocene (9,475–7,685 years BP) unit. The stratigraphic relationship between these units has not been established. Results revealed that the Valentín Formation deposits show numerous flow sedimentary structures associated with rapidly aggrading anastomosed and ephemeral meandering river systems with thick unconfined mud-clay-sandy floodplains, vertical accretion, aeolian deposition, and a low gradient (Order C, Nanson and Croke, 1992). A subordinate share of these deposits indicated the existence of a small (<10 km2) and relatively shallow (<10 m) lake environment in the southeastern sector of the valley during the early to mid-Holocene. The lacustrine phase was initially characterized by calm, cold, and occasionally anoxic fresh waters that would have been associated with low flow and limited erosive capacity of the San Juan River. In Sector 1 (Pleistocene unit), the lower half of the Valentín Formation outcrop comprises the facies associations CH(SB), LV, FF1, CHA, FF2, and FE (Table 3). This sequence display channels characterized by monoepisodic filling immersed in thick floodplain facies, which would indicate the dominance of vertical aggradation. The floodplain (inter-channel areas) can be divided into three zones: a proximal zone, dominated by sandy facies deposited by main channels overflows, marked by the frequent presence of CS, CR, and to a lesser extent LV associations (Table 3); a transition zone, towards less energetic areas in an intermediate to a distal position, characterized by the FF1 association, with abundant vertical bioturbation and frequently affected by overflows from a network of secondary clay channels that cut through the flood plain (CHA); and finally a distal area marked by the associations FF2 and FE with deposition by settling in ephemeral pools and aeolian aggradation. The development of monoepisodic channels within massive floodplains, the preservation of the upper surface of flow sedimentary structures, and the presence of several buried incipient paleosols suggest high sedimentation rates (Nadon, 1994; Gibling, 2006). From the numerical ages and the stratigraphic thickness, we estimated an average sedimentation rate of 7 mm/year for the Pleistocene unit (16.770 a 15.160 cal. years BP). Some of these immature paleosols, called protosols according to the classification of Mack et al. (1993), showed accumulation of illuvial clay indicative of an argillic horizon, although poorly developed, therefore called argillic protosol. Other features observed were desiccation cracks, raindrop marks, and the development of cyclic greenish and reddish muds in the floodplain that, together with argillic protosols, would indicate semi-arid to possibly semi-humid seasonal conditions (Mack et al., 1993). However, the intercalation of the aeolian facies on top of aggradation cycles in the floodplain, and the presence of syngenetic gypsum, would reflect a greater degree of aridity and a marked seasonality (Tripaldi et al., 2001). The upper half of the Pleistocene unit composed of the LA, CS, CR, FF1, FF2, and FE facies associations represent an environmental change to more arid conditions. This sequence characterizes by lateral accretion bars (point bar, association LA) and greater development of aeolian facies (FE association) that are interrupted by the deposition of fine-grained alluvial facies in ephemeral pools and poodles (FF2 association). These fine-grained deposits show rainwater droplet marks and syngenetic gypsum in the form of veins and coatings, indicating seasonality. Salinas (1979) observed that grain size distributions (histograms) from some samples of the Valentín Formation were bimodal with the main mode in the very fine silt fraction and a secondary mode in very fine sands. Salinas (1979) interpreted this bimodality as a result of both fluvial and aeolian sedimentary inputs. The presence of gypsum in specks, veins, rosettes, and forming coatings on top of some channels, and the predominantly yellowish to reddish coloration of the deposits would be indicative of oxidizing conditions in a more arid and markedly seasonal climate (Watson, 1992). In Sector 5 (Fig. 4), close to the Zonda gorge, the Holocene unit of the Valentín Formation develops a shallowing lacustrine sequence characterized by the association of facies FLS (sub-littoral), FLM (sub-littoral to littoral), BD (littoral to supra-littoral), and FF2 (floodplain). The immediate passage from coarse alluvial channel facies (GB association) to a relatively deep lake environment (FLS association) suggests that the formation of the lake would have occurred abruptly, shortly before 9,475 years BP (Blanc and Perucca, 2017). The impressions of vegetal remains parallel to lamination found in the FLS association resemble the leaves and stems of reeds. The riparian nature of reeds and the integrity of their remains reflected in the clarity and detail of their casts would indicate a parautochthonous origin with little or no transport before deposition. The clear-cut lamination and the fine-grained size of sediments (silts and clays) would indicate deposition in calm waters. The greenish-white coloration of the deposit suggests slightly reducing conditions, possibly caused by localized anoxia related to the decomposition of organic matter (Bridge and Demicco, 2008). The passage to the reddish-brown FLM association, which conformably overlies the FLS association, would mark the opening of the system and the entry of a higher water and sediment input, causing the oxygenation of the water column. We observed no evidence of subaerial exposure in the FLS and FLM associations so that these deposits would have formed below the zone of annual fluctuation of the water level on the sublittoral belt. On top of the FLM association, sands with flow sedimentary structures interbedded with laminated muds showing load-casts linked to rapid sedimentation were interpreted as sandy bar deposits (BD association; Wright, 1977; Orton and Reading, 1993). The superimposed iron oxides on the lacustrine sequence deposits would indicate a change from reducing to oxidizing conditions, possibly as a result of an eventual lowering of the water table after the lake filled up with sediments. We estimated an average accumulation rate of 2.1 mm/year for this lake, a value significantly lower than the estimations for the Pleistocene unit (7 mm/year). Towards the top of the sequence, the FF2 association represents the progradation of a distal fluvial plain as deduced from the presence of millimetric layers of organic matter, high bioturbation, and the development of incipient paleosols with clay translocation (argillic protosol). In Sector 2, the deposits of the Holocene unit show horizontal lamination and little development of lithosomes (some overflow lobes), indicating that deposition from torrential floods would be one of the dominant aggradation mechanisms. This sequence was interpreted as a fluvial system with multi-episodic channels and unconfined sandy floodplains, with significant vertical accretion and aeolian sedimentation (order C, Nanson and Croke, 1992). In summary, the paleoclimatic record of the Pleistocene indicates a progressive aridization, from seasonal semi-arid conditions ( 16,800 years BP) to more arid conditions marked by a significant increase in aeolian deposition and the presence of syngenetic gypsum in channel facies ( 15,000 years BP). The Holocene record shows arid to semi-arid seasonal climatic conditions (based on the accumulation of illuvial clay in some paleosols, fossil content, raindrop marks, and desiccation cracks) during the early to mid-Holocene ( 8,300 to 8,000 years AP). The Holocene unit would have started its deposition shortly before 9,475 years BP with a sudden increase in the local base level and the formation of a small lake in sector 5. In sector 2, the transition from alluvial fan facies to the fine-grained deposits of the Valentin Formation would have occurred 1,100 years later, between 8,330 and 8,180 years BP under markedly seasonal arid climatic conditions. The beginning of the 8,200 BP cold period (Beget, 1983; Douglas et al., 2015; among others) would have caused an increase in river flow and sedimentary input to the lake. As a result, the lake in sector 5 filled up with sediment around 8,100 years BP, giving way to a fluvial plain in a relatively cold, arid to semi-arid, and markedly seasonal climate. Finally, the maximum aggradation (registered in sector 6) would have occurred 600 years later, shortly after 7,685 years BP (Blanc and Perucca, 2017) in a seasonal arid climate. The deposition of the Valentín Formation would have occurred in episodic aggradation events partially coincident with the Last Glacial Maximum and the 8,200 BP cold period and possibly associated with non-catastrophic ruptures and reworking of the fine-grained deposits produced by natural damming of the San Juan River, upstream from the Ullum-Zonda valley (Colombo et al., 2000). This process would also have been favored by tectonic deformation and uplift in the eastern Precordillera, and during the Holocene, by an increase in seasonal torrential rainfalls, which would have contributed to obstructing with debris the San Juan river flow through the Zonda gorge. The alluvial fraction of the illite-chlorite-kaolinite clay assemblage described in the Valentín Formation by Salinas (1979) would locate the main provenance area of these sediments in the glaciated regions of the Andes Mountains and a secondary sedimentary input from the Precordillera.